AGEING IN CITIES: CONTRIBUTING FACTORS AND CHALLENGES - Vynohradova, Mariia (Collection of scientific papers «ΛΌГOΣ», 2022)
Ageing in cities is comparatively a new area of research that focuses on the trends and prospects of ageing in the cities. The ageing of society is a challenging phenomenon, which characterizes the current stage of the global demographic transition. But this process should not be considered one-sided as a problem only. In general, longevity is the result of economic development and technological progress. By 2050, the percentage of the world’s population that is aged 65 and older will grow from the current 9.4% to about 16.0%. The global number of people aged 80 years and older is assumed to more than double by 2030, with a projection of nearly 426 million in 2050, which is more than three times the relatively estimated number in 2019 of 143 million [1].